2017
DOI: 10.1159/000484023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mental Disorders Using Proton Magnetic Resonance Spectroscopy in Dialysis and Predialysis Patients

Abstract: Background/Aims: Psychological complications are prevalent in patients with chronic kidney disease (CKD). This study aimed to investigate mental disorders in stage 4-5 CKD patients, to detect metabolite concentrations in the brain by proton magnetic resonance spectroscopy (1H-MRS) and to compare the effects of different dialysis therapies on mental disorders in end-stage renal disease (ESRD). Methods: The sample population was made up of predialysis (13), hemodialysis (HD) (13), and peritoneal dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For example, previous voxel-based morphometrics, surface-based morphometrics, and diffusion tensor imaging studies have revealed defects in gray matter volume and reduced cortical thickness [11], as well as reduced white matter integrity [12] in ESRD patients. In addition, various analyses, including arterial spin labeling [13], magnetic resonance spectroscopy [14], and single-photon emission tomography [15], have found abnormalities in brain metabolism and function in ESRD patients treated with HD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous voxel-based morphometrics, surface-based morphometrics, and diffusion tensor imaging studies have revealed defects in gray matter volume and reduced cortical thickness [11], as well as reduced white matter integrity [12] in ESRD patients. In addition, various analyses, including arterial spin labeling [13], magnetic resonance spectroscopy [14], and single-photon emission tomography [15], have found abnormalities in brain metabolism and function in ESRD patients treated with HD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies with voxel‐based morphometry, surface‐based morphometry, and diffusion tensor imaging (DTI) revealed gray matter volume deficits (Qiu et al., 2014; L. J. Zhang et al., 2013), decreased cortical thickness (Dong et al., 2018), and reduced white matter integrity (Drew et al., 2017; R. Zhang et al., 2015) in patients with ESRD. In addition, cerebral metabolic and functional abnormalities were demonstrated in ESRD patients who underwent HD using different analyses, including arterial spin labeling (Jiang et al., 2016), magnetic resonance spectroscopy (C. Y. Zhang et al., 2017), and single‐photon emission tomography (Polinder‐Bos et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various analysis methods also can help to identify brain metabolism and function abnormalities in ESRD patients receiving HD treatment. These methods include arterial spin labeling [ 14 ], magnetic resonance spectroscopy [ 15 ], and single photon emission computed tomography [ 16 ]. Moreover, fractal analysis can be utilized for revealing the complexity and dynamics of EEG signals in ESRD patients to fully comprehend the function and connectivity of brain networks.…”
Section: Introductionmentioning
confidence: 99%